Peary caribou, muskoxen and Banks Island forage: Assessing seasonal diet similarities - Larter, Nicholas C.; Nagy, John A. (Rangifer, 1997)
Peary caribou (Rangifer tarandus pearyi) and muskoxen {Ovibos moschatus) on Banks Island had considerable similarity in their annual diets, with monthly similarities ranging from 17.8-73.3%. Diet similarity was more pronounced in areas of high muskox density {ca. 1.65/km2) than in areas of low muskox density {ca. 0.4/km2). Willow (Salix arctica) and sedge (Carex aquatilis and Eriophorum spp.) represented >80% of the monthly diet of muskoxen. The caribou diet was more diverse, and was dominated by sedge, willow, Dryas integrifolia, and Oxytropis maydelliana, Lichen use was rare, likely as a consequence of low availability on Banks Island. Lichen standing crop was estimated at 2.96 g/m2. The differences in muskox diet between high and low density areas could not be explained by differences in forage distribution or standing crop. We discuss diet similarities of caribou and muskoxen and potential consequences for the current Peary caribou population in relation to winter weather conditions and increasing muskox density.
Keywords: diet overlap; food competition; arctic; Northwest Territories; Rangifer tarandus pearyi; Ovibos moschatus